Implementasi Metode Mengajar Rasulullah dalam Pembelajaran Pendidikan Agama Islam di SMA Negeri 1 Perbaungan - Putri, Ayilzi; Harahap, Ahmad Yunus Mokoginta (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to examine the implementation of the Prophet's teaching method in Islamic Religious Education (PAI) learning and its impact on the formation of student character at SMA Negeri 1 Perbaungan. Departing from the urgency of character education, this study uses a qualitative method with a case study approach. Data was collected through observations, interviews, and documentation from teachers, students, and vice principals. The results of the study show that PAI teachers in this school dominantly apply the five main methods of the Prophet, namely exemplary (uswatun hasanah), gradual, discussion and question and answer, giving advice (mau'izah), and motivation and threats (targhib and tarhib). These methods have proven to be effective in shaping students' religious character, improving understanding of Islamic teachings, and creating an interactive learning environment. The success of the implementation is supported by the creativity and example of teachers, student activity, and full support of the school. Meanwhile, the obstacles faced include low interest in reading students, the passive attitude of some students, and lack of supervision over the use of technology. Overall, this study shows that the teaching method of the Prophet not only relevant, but also highly applicable in the context of formal education to shape the character of students in the modern era. The results of this study contribute to the development of an effective PAI learning model oriented towards the formation of noble morals.